Efficient removal of titanium and vanadium impurities in aluminum melt by adding Al–B alloy containing AlB12 - Mengping Duan; Zibin Zuo; Xianjun Lei; Bin Yang; Baoqiang Xu; Chengcheng Fu (Journal of Materials Research and Technology)
The titanium and vanadium impurities in aluminum melt can be minimized by adding an AlB12-containing Al–B alloy. In this study, we investigated the removal mechanism of titanium and vanadium impurities associated with the element migration and phase transformation, as well as the microstructural evolution of VB2 following the addition of an Al–B alloy to an aluminum melt. Thermodynamics calculations revealed that titanium preferentially interacts with AlB12 to form titanium-boron compounds and was removed, and then AlB12 interacts with vanadium. Line-scanning analysis revealed that the product ring thickened and the AlB12 particles gradually dissolved and eventually disappeared with increasing holding time, with the boron combining with the titanium and vanadium to form a compound that precipitated and then settled. With the increase of Al–B alloy addition and the extend of holding time, the removal efficiencies of titanium and vanadium reached 93.3% and 98.0%, respectively, and then stabilized. The titanium and vanadium contents were reduced to 1 and 2 ppm at 1073 K when 0.07 wt.% B was added for a holding time of 60 min, with corresponding removal efficiencies of 93.3% and 98.0%, respectively. This study reveals the mechanism of vanadium and titanium removal from aluminum melt, providing theoretical and experimental basis for the preparation of high-purity aluminum by removing vanadium and titanium with removal agents.